Robust optimal attitude determination using interval analysis. Issue 6 (15th March 2022) - Ghadiri, Hossein; Esmaelzadeh, Reza; Zardashti, Reza
Abstract: The attitude determination of the satellite leads to solving the Wahba problem. The Wahba problem utilizes a set of at least two independent sensor measurements and reference vectors for attitude determination. These input vectors are not accurate due to sensor noises, misalignment, and low-order approximations. But these uncertainties do not consider in the classic Wahba problem directly. This paper presents a robust multi-objective optimization method for solving the static attitude determination with bounded uncertainty. The bounded uncertainty due to modeling error, measurement noise, and biases have modeled using interval analysis. Then, the Wahba problem is reformulated to a robust multi-objective optimization problem that consists of two performance indexes. The effectiveness of the proposed approach is evaluating by solving several examples.